Legalitas Tindakan Pemerintah Daerah Dalam Pengalihan Fungsi Trotoar Kota Ambon - Samal, Radhi Rafiq Defrian; Irham, Muhammad; Matitaputty, Merlien Irene (PATTIMURA Law Study Review, 2024)
ABSTRACT: Article 34 paragraph 3 of the Constitution of the Republic of Indonesia states that the state is responsible for providing health service facilities and adequate public service facilities to the community. Furthermore, Article 45 paragraph 1 letter a of Law Number 22 of 2009 concerning Road Traffic and Transportation "states that supporting facilities for the implementation of road traffic and transportation include sidewalks, the provision of which is provided by the local government. “Article 113 paragraph 1 letter a government regulation number 79 of 2013 concerning Road Traffic and Transportation Networks states that sidewalks are also a form of public service provided by the government as supporting facilities for road traffic and transportation in the form of provisions for pedestrians. Article 11 Paragraph 2 of Law Number 38 of 2004 concerning Roads "states that sidewalks are useful spaces for pedestrians. In accordance with the problems raised, the type of research used in this writing is normative juridical legal research. Legal research is a process of discovering legal rules, legal principles and legal doctrines in order to answer the legal issues faced. The Ambon City Government regarding changing the function of sidewalks in Ambon City is currently not in accordance with Article 4 paragraphs 3 and 4 of Ambon City Regional Regulation No. 10 of 2014 concerning the Arrangement of Street Vendors, which states (3) Locations that cannot be designated as business premises for street vendors The five are as follows: within government agencies, within schools, within places of worship, around market locations, on roofs and sewers, in city parks and green lanes, around monuments and hero's graves, throughout the body road.